2021
DOI: 10.32535/jicp.v4i2.1257
|View full text |Cite
|
Sign up to set email alerts
|

Fraud in Financial Institutions

Abstract: Fraudulent acts in financial institutions have often occurred, there are even some financial institutions who try to clarify related to the frauds that occur in these financial institutions. This study describes fraudulent acts that occur in conventional financial institutions, by taking data from the official websites of each financial institution, by reading reports Good Corporate Governance (GCG) of banks. Data collection from 2015-2019. The research conducted is descriptive quantitative research, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…These factors are known as the fraud triangle. Cressey found that people commit fraud when they have financial problems that can't be solved, believe that their problem can be solved quietly based on their respective job/position (Pradesyah et al, 2021).…”
Section: Agency Theorymentioning
confidence: 99%
“…These factors are known as the fraud triangle. Cressey found that people commit fraud when they have financial problems that can't be solved, believe that their problem can be solved quietly based on their respective job/position (Pradesyah et al, 2021).…”
Section: Agency Theorymentioning
confidence: 99%
“…This rule is commonly referred to as academic ethics. Ethics are moral principles that describe what is right or wrong in regulating one's behavior (Plante & McCreadie, 2019). Higher education often involves academic ethics, which generally refers to the standards of behavior required in academia to promote the integrity of educational practice (Asamoah, 2019).…”
Section: Violations Of Academic Ethicsmentioning
confidence: 99%
“…This is evident from the financial sector in Indonesia which is dominated by the banking sector. The development of banking in Indonesia has spread significantly measured by the increase of financial institution in society (Pradesyah, Yuslem, & Batubara, 2021). Based on the Law of the Republic of Indonesia No.…”
Section: Introductionmentioning
confidence: 99%